Growth models fitted to Dipturus chilensis length-at-age-data support a two phase growth - AVERSA,MARINA I (Sociedad de Biología de Chile, 2011)
Age and growth for the beaked skate was estimated from bands in the vertebral centra of 689 individuals obtained from incidental catches of the Argentine hake (Merluccius hubbsi) fishery. Age bias plots and indices of precision indicated that ageing method was precise and unbiased (% CV = 3 % PA = 82.09 %). Edge and marginal increment analysis of the vertebrae support the hypothesis of annual band pair deposition. Three growth models were fitted to length-at-age and the two-phase growth model produced the best fit. This feature has never been described before for D. chilensis and can be related to changes in energy allocation and the shift from juvenile to adult phase. The unrealistic biological estimates of the von Bertalanffy growth model illustrates the importance of fitting alternative models to the data. Female beaked skates reached greater size in length (L∝) as well as in disc width (L∝ = 138.2 cm; DW∝ = 92.46 cm) and have lower growth rate (k = 0.08 yr-1) than males (L∝ = 106.7 cm; DW∝ = 74.52 cm; k = 0.121 yr-1). This study provides basic information on age and growth for the beaked skate, D. chilensis, which were previously not available for its south Atlantic range of distribution.